2005
DOI: 10.1016/j.neuron.2004.12.049
|View full text |Cite
|
Sign up to set email alerts
|

GABA Transporter Currents Activated by Protein Kinase A Excite Midbrain Neurons during Opioid Withdrawal

Abstract: Adaptations in neurons of the midbrain periaqueductal gray (PAG) induced by chronic morphine treatment mediate expression of many signs of opioid withdrawal. The abnormally elevated action potential rate of opioid-sensitive PAG neurons is a likely cellular mechanism for withdrawal expression. We report here that opioid withdrawal in vitro induced an opioid-sensitive cation current that was mediated by the GABA transporter-1 (GAT-1) and required activation of protein kinase A (PKA) for its expression. Inhibitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
87
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(93 citation statements)
references
References 51 publications
6
87
0
Order By: Relevance
“…mice were treated with hypertonic sucrose (50 mM) before and during ME desensitization. We have reported previously that treatment of slices with hypertonic sucrose (50 mM) impairs vesicle recycling and presumably endocytosis (Bagley et al, 2005b). Similar to blocking dynamin-dependent endocytosis with DYNi peptide, hypertonic sucrose did not affect MOR activation of GIRK currents or acute desensitization but significantly enhanced the rate of MOR resensitization (Fig.…”
Section: Disruption Of ␤Arrestin-2-dependent Receptor Trafficking Accmentioning
confidence: 57%
“…mice were treated with hypertonic sucrose (50 mM) before and during ME desensitization. We have reported previously that treatment of slices with hypertonic sucrose (50 mM) impairs vesicle recycling and presumably endocytosis (Bagley et al, 2005b). Similar to blocking dynamin-dependent endocytosis with DYNi peptide, hypertonic sucrose did not affect MOR activation of GIRK currents or acute desensitization but significantly enhanced the rate of MOR resensitization (Fig.…”
Section: Disruption Of ␤Arrestin-2-dependent Receptor Trafficking Accmentioning
confidence: 57%
“…ME-induced currents reversed near the equilibrium potential for potassium (À88±5 mV; n ¼ 5) in the presence of the GAT inhibitor, NO-711 (10 mM) indicating that the more negative reversal potentials in morphine pretreated rats were caused by opioid inhibition of inward current mediated by GAT. However, intermittent morphine does not appear to induce GAT currents as large as those observed by Bagley et al (2005b) because ME-induced currents reversed at À111±3 mV, whereas the reversal potentials for MEinduced currents were generally more negative than À120 mV in rats pretreated with continuous morphine administration. In order to determine the amplitude of GAT currents in rats pretreated with morphine injections, the GAT inhibitor NO-711 (10 mM) was superfused in the presence of the GABA B antagonist CGP-55845 (10 mM).…”
Section: Morphine Pretreatment Increases Opioid-mediated Girk Currentsmentioning
confidence: 72%
“…Previous studies have shown that continuous administration of morphine induces an additional opioid-sensitive current in the PAG that is associated with the GABA transporter (GAT) (Bagley et al, 2005b). This cation current is inhibited by opioids and contributes to ME-induced responses by augmenting the outward current elicited by ME and shifting the reversal potential to more hyperpolarized potentials than the expected value for a potassium current (ie GIRK).…”
Section: Morphine Pretreatment Increases Opioid-mediated Girk Currentsmentioning
confidence: 99%
“…However, the amplitudes of our ME-induced GIRK currents at À40 mV, a potential where the nonselective cation current is minimal , were also not different between tolerant and control rats. One reason for this discrepancy in m-opioid receptor coupling to GIRK channels may be that studies where decreased m-opioid receptor coupling to GIRK channels are observed use slow release preparations that release morphine constantly over 3-5 days (Christie et al, 1987;Chieng and Christie, 1996;Chieng and Williams, 1998;Ingram et al, 1998;Hack et al, 2003;Bagley et al, 2005). This would lead to a different pattern of opioid exposure compared to our repeated intermittent injection procedure, and longer opioid exposure may result in additional cellular changes that promote opioid receptor desensitization.…”
Section: Discussionmentioning
confidence: 99%
“…These in vivo studies are supported by in vitro data showing that chronic morphine administration induces profound changes in ventrolateral PAG neurons, including decreased opioid activation of GIRK channels (Chieng and Christie, 1996;Ingram et al, 1998;Hack et al, 2003;Bagley et al, 2005) and increased opioid inhibition of presynaptic GABA release (Chieng and Christie, 1996;Ingram et al, 1998;Hack et al, 2003;Bagley et al, 2005). Studies with GIRK knockout mice have demonstrated that postsynaptic m-opioid receptor coupling to the GIRK channel is important for the antinociceptive effects of morphine (Ikeda et al, 2002;Blednov et al, 2003;Mitrovic et al, 2003;Marker et al, 2005) and suggest that postsynaptic m-opioid receptor coupling to GIRK channels in PAG neurons may contribute to opioid tolerance.…”
Section: Introductionmentioning
confidence: 87%